Appreciation of Art as a Perception Sui Generis: Introducing Richir’s Concept of “Perceptive” Phantasia - Ekweariri, Dominic (Frontiers in Psychology, 2021)
In the “origin of the work of art” Heidegger claimed that the work of art opens to us the truth of Being, the opening of the world. Two problematics arise from this: first his idea of “world-disclosure” evoked a sense of everydayness (which captures, for me, the idea of credulism in perception). Second the sense of truth, Being or world are metaphysically condensed. Hence the question: how then could the “truth of Being” or the “world” that art works reveal be experienced? Among other ways (mimesis, imagination, perception etc.) by which art works are experienced, I choose to examine perception since it confirmed this idea of everydayness. The questions that confronts us to this effect are: can perception lead us into, to encounter, this world opened by art works? Does the nervous/visual system suffice to enter into that world in which the artist invites us? This is where Richir becomes important. In response to the first problem, he shows that the “perception” (experience) of art works is beyond mere everydayness since art works open for us a world that “never was” and “never will be” (i.ei.”virtuality” and not a veridical sense of everydayness as captured in the perceptive act that is object-related). This is because the material stuff or object given in perception is neutralised by the phantasia to become what Richir calls Sache. This Sache is in itself a phenomenon that is disclosed in art works. In response to the second problem, Richir shows how art works cannot disclose just metaphysical categories of Being, truth or world. The disclosure has to be phenomenological, corporeal and affective. He therefore proposes another mode of “perception” beyond mere perception in a revolutionary interpretation of the husserlian“perceptive” phantasia. With this he shows how the aformentioned metaphysical condensations are livable in experience. I concretize this with an illustration from the theatre. Finally I suggest participation as a phenomenological approach that can make both Heidegger’s and Richir’s intuitions meaningful.